ADVANCEMENTS IN WASTEWATER TREATMENT: SCIENTISTS HARNESSING LOCAL RESOURCES FOR POLYPHOSPHATE FILTERS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article discusses the research conducted by scientists in the field of wastewater treatment, specifically focusing on the development of polyphosphate filters derived from locally available raw materials. The utilization of such filters has the potential to revolutionize wastewater treatment processes by improving efficiency, reducing costs, and promoting sustainability. The article explores various case studies, including the use of agricultural by-products, industrial waste, and naturally occurring minerals as potential sources for these filters. The challenges faced by researchers in terms of optimization, durability, and regulatory compliance are also highlighted. The conclusion emphasizes the promising prospects of sustainable wastewater treatment technologies through the integration of polyphosphate filters derived from local raw materials.